Changes in instrumentally and classically conditioned limb-flexion responses following inferior olivary lesions and olivocerebellar tractotomy in the cat - Voneida, TJ (J Neurosci, 1990)
Lesions were placed in various parts of the inferior olivary nucleus and olivocerebellar tract in an attempt to define further the role of the inferior olive in the performance of a conditioned limb-flexion response (LFR) in cats. Thirty-two cats were trained to make an LFR using either classical or instrumental conditioning. The conditioned stimulus (CS) was a tone, and the unconditioned stimulus (US), a shock to the forelimb. Following training, lesions were placed in various parts of the inferior olivary nucleus in 20 animals (radio frequency lesions, 17; electrolytic lesions, 3). Midline section of the olivocerebellar tract was carried out in 12 animals. The degree of conditioned-response (CR) loss resulting from a given lesion was closely related to the precise locus of the lesion. Rostromedial olivary lesions, which included the spino- and cortico-olivary forelimb projection zones and the olivocerebellar projection area, resulted in varying degrees of CR loss (from partial to near total), deregulation of response latency, and a significant reduction of response amplitude. The CR deficit and degree of post-operative CR recovery were directly related to the extent of damage to this part of the rostromedial olive. Lesions restricted to the caudal olive or to caudal levels of the olivo- cerebellar tract resulted in no postoperative CR deficits. Animals with caudal lesions, however, showed more severe general motor deficits postoperatively than did those with rostromedial lesions and loss of the CR. Prolonged training of animals with the most complete CR deficits resulted in some relearning, but response patterns were typified by long-latency, low-amplitude CRs and a highly unstable response pattern.